Progressive Agrarian Law as a Concept to Attain Social Justice - Muh Afif Mahfud (Universitas Negeri Semarang, 2022)
The management of Indonesian agrarian law has created discrepancy of resources ownership or injustice. This article offer a new perspective namely progressive agrarian law. This is a normative juridical research with conceptual approach by using primary, secondary and tertiary data. Those data are collected through literature research and analyzed with content analysis. Based on analysis, it can be concluded that there are several characteristic of progressive agrarian law, namely : (1) dynamic and contextual and respect the diversity because this consider social-political-cultural and economical condition of the society; (2) agrarian justice oriented to solve inequality of agrarian resources by doing affirmative action; (3) emphasize the importance of conscience in law making and law enforcement (involve intellectual, emotional and spiritual quotient); (4) give the chance for law enforcement to do rule breaking toward injustice regulation (substantive justice orientation); (5) pay attention disadvantage person (poor people) who lives under poverty and experience injustice.